2019
DOI: 10.1186/s13034-019-0298-8
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and risk behaviors of children in rural China with different patterns of parental migration: a cross-sectional study

Abstract: BackgroundOne in seven members of China’s population are migrants. There are an estimated 41 million children left behind in rural areas who are living without one or both of their parents. The impact of two- and single-parent migration on child mental health and risk behaviors is unclear. The aim of this study was to compare the mental health and risk behaviors among children whose parents are either both migrating (B-LBC), have one parent migrating (O-LBC) or those whose parents do not migrate (N-LBC).Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…Most of the selected children in these previous studies were concentrated in only one city or in several cities in one province, such as Chongqing, Hunan, Sichuan and other places [11]. In addition, the standards and the results of previous research on depression, anxiety, or personality traits of the LBC were inconsistent [12,13]. To fill in the research gaps, the proposed study aimed to conduct a national study using an international standardized measure to explore the emotional and behavioral problems and related risks factors for the LBC using resilience framework.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the selected children in these previous studies were concentrated in only one city or in several cities in one province, such as Chongqing, Hunan, Sichuan and other places [11]. In addition, the standards and the results of previous research on depression, anxiety, or personality traits of the LBC were inconsistent [12,13]. To fill in the research gaps, the proposed study aimed to conduct a national study using an international standardized measure to explore the emotional and behavioral problems and related risks factors for the LBC using resilience framework.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies in China and abroad, children who are left behind encounter a range of problems. LBC tend to display more emotional, behavioral, and learning problems, such as depression, nonsuicidal self-injury, and game addiction (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…As estimated, in 2018, the number of LBC has reached 69 million [4]. Previous studies found that parental absence would put children at risk for mental health disorders and problem behaviors [5,6]. A meta-analysis [7]demonstrated that LBC were more likely to develop depression, anxiety, suicidal ideation, conduct disorders and substance use.…”
Section: Introductionmentioning
confidence: 99%